Pengaruh Karakteristik Individu terhadap Komitmen Organisasional yang Dimediasi Etos Kerja (Studi pada Pegawai PPPK Dinas Pendidikan Kabupaten Malang) - Survival, Survival; Herfan, Mohammad; Anam, Choirul (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study investigates the influence of individual characteristics on organizational commitment, with work ethic as a mediating variable, among Government Employees with Work Agreements (PPPK) at the Education Office of Malang Regency. Previous research has shown inconsistent findings regarding the direct relationship between personal traits and organizational commitment, highlighting a theoretical gap in understanding how individual factors contribute to employees’ dedication. Using a quantitative explanatory approach, data were collected from 58 PPPK employees through structured questionnaires and analyzed using Structural Equation Modeling with the SmartPLS 4.0 software. The findings reveal that individual characteristics have a positive but statistically insignificant effect on organizational commitment, suggesting that personal traits alone are not sufficient to determine employees’ commitment. However, individual characteristics significantly influence work ethic, and work ethic, in turn, has a strong and significant impact on organizational commitment. Furthermore, the analysis confirms that work ethic fully mediates the relationship between individual characteristics and organizational commitment. These results underscore the critical role of ethical behavior in translating individual attributes into meaningful organizational outcomes. The study contributes to the literature by demonstrating the indirect influence of individual traits through work ethic and offers practical recommendations for organizations to foster commitment by cultivating a strong ethical climate.